Entailment Is Not Evidence - Reed, Thomas (Sophia, 2025)
Mike Almeida recently published a paper entitled "Evil Is Not Evidence," but that title rather understates his conclusion. He argues that no "states of affairs constitute any (non-trivial) evidence for or against the existence of God" (p. 1, original emphasis) (bare page references are to Almeida, 2022). It of course follows from that that evil is not evidence against the existence of God, but it also follows that apparent design or even direct experience of God are not non-trivial evidence for the existence of God. While his title suggests a conclusion favorable to theists, it might in fact be a poisoned pawn, since his conclusion also entails that arguments from design or religious experience are completely hopeless. Such a radical transformation of the traditional debate between theists and atheists bears scrutinizing. In particular, Almeida appeals to a notion of evidence that I'm going to argue is mistaken.The basic argument I am going to make is that Almeida is taking strict implication to be an evidentially relevant relation. In particular he's embracing one of the paradoxes of strict implication, that a necessary truth is strictly implied by any claim whatever, and he's assuming that not only is the inference valid, pace relevance logics, but that it provides evidence for the implied proposition. I'm going to argue this is a mistake. Even if we grant that the inference is valid, we shouldn't accept that it provides evidence.